Body image perception and satisfaction in elite rhythmic gymnasts: a controlled study - Borrione, P.; Battaglia, C.; Fiorilli, G.; Moffa, S; Despina, T.; Piazza, M.; Calcagno, G.; Di Cagno, A. (Medicina dello Sport, 2013)
SUMMARY Aim. Participation in competitive sport has been frequently linked to distortions in body image. The aim of this study was to verify the correctness of the perception of one's own body image and level of satisfaction to foresee eating disorders in elite rhythmic gymnasts, as well as carry out potential preventive strategies.